2020
DOI: 10.3390/cells9102236
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Diabetes- and TGF-β1-Induced Renal Damage

Abstract: While females are less affected by non-diabetic kidney diseases compared to males, available data on sex differences in diabetic nephropathy (DN) are controversial. Although there is evidence for an imbalance of sex hormones in diabetes and hormone-dependent mechanisms in transforming growth factor β1 (TGF-β1) signaling, causes and consequences are still incompletely understood. Here we investigated the influence of sex hormones and sex-specific gene signatures in diabetes- and TGF-β1-induced renal damage usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 81 publications
2
30
0
Order By: Relevance
“…54 The sex differences do not significantly affect lifespan in laboratory mice 54 and our findings that female eI-F2A-KO mice have lower longevity in comparison with the eIF2A-KO male mice suggests that eIF2A may affect sexspecific signaling pathways. Accumulating data do reveal sex specific difference in several signaling pathways (such as e.g., TGF-βsignaling 55 ) and suggest, for example, that diabetes may be associated with an imbalance in sex hormone levels, but it has not yet been conclusively clarified how the levels of testosterone and/or estrogen and their respective receptors and the imbalance between them are exactly related to the differences in disease progression in both sexes. 56,57 We also examined if locomotor activity and daily/circadian rhythms of locomotor activity were affected in eI-F2A-KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…54 The sex differences do not significantly affect lifespan in laboratory mice 54 and our findings that female eI-F2A-KO mice have lower longevity in comparison with the eIF2A-KO male mice suggests that eIF2A may affect sexspecific signaling pathways. Accumulating data do reveal sex specific difference in several signaling pathways (such as e.g., TGF-βsignaling 55 ) and suggest, for example, that diabetes may be associated with an imbalance in sex hormone levels, but it has not yet been conclusively clarified how the levels of testosterone and/or estrogen and their respective receptors and the imbalance between them are exactly related to the differences in disease progression in both sexes. 56,57 We also examined if locomotor activity and daily/circadian rhythms of locomotor activity were affected in eI-F2A-KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…In nondiabetic conditions, men with chronic kidney disease of various etiologies show a more rapid decline in renal function than women 21 ; however, a study suggested diabetic nephropathy progression to be faster in women, 21 and the difference might be related to female hormones. A recent study published in the journal Cells investigated the extent to which sex hormones play a role in sex differences in both diabetes and transforming growth factor β1 (TGF‐β1)‐induced renal damage 22 . They found that both genetic repertoire and sex hormones can determine sex differences in diabetic nephropathy, and hormones and sex in combination with TGF‐β1 dose determine whether TGF‐β1 exerts pro‐ or antifibrotic effects.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 is a major cytokine secreted by mesangial cells that mediates the development of DN [33] . TGF-β1 is a key cytokine mediating collagen deposition in kidney, including promoting the production of ECM, inhibiting the degradation of ECM and participating in renal brosis [34,35] . ECM of DN patients is produced by mesangial cells and mainly consists of bronectin, type IV collagen and a small amount of type I collagen.…”
Section: Discussionmentioning
confidence: 99%